Peningkatan Literasi Lingkungan Pada Siswa SMA Negeri 4 Ambon Sebagai Upaya Mengurangi Pencemaran Sampah Plastik di Teluk Ambon - Marlin Chrisye Wattimena; Degen E. Kalay; Harold J. D. Waas; Eva S. Ratuluhain; Simon Tubalawony; Ronald D. Hukubun (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
One possible way for school students obtaining environmental awareness is from environmental knowledge taught in classes. The Community Service Program of Department of Marine Science of Fisheries and Marine Science Faculty, Pattimura University in the form disseminations on literacy of coastal environment aimed to encourage school students to be pioneers and drivers for coastal conservation and beach clean-ups in their local community in Ambon Bay. The materials used in the disseminations focused on understanding coastal environment in Ambon Bay, and sources and types of pollutants in the system. The materials also covered the impacts of the coastal pollution and how to address it including to reduce and solve the pollution in Ambon Bay. At the end of the disseminations, the questions-and-answer session was conducted to evaluate the understanding of students on the knowledge of marine pollution management in Ambon Bay,